Control of the spread of vancomycin-resistant enterococci in hospitals: epidemiology and clinical relevance - Mutters, Nico T.; Mersch-Sundermann, Volker; Mutters, Reinier; Brandt, Christian; Frank, Uwe (Deutsches Ärzteblatt, 2013)
Enterococci are gram-positive, facultative anaerobic chain cocci with extremely high environmental resistance (1). Enterococci are known to cause, among other things, urinary tract infections, neonatal infections, and endocarditis (2). However,...
Gesehen am 17.11.2021